Is primary angioplasty cost effective in the UK? Results of a comprehensive decision analysis. Issue 10 (23rd August 2007) - Bravo Vergel, Yolanda; Palmer, Stephen; Asseburg, Christian; Fenwick, Elisabeth; de Belder, Mark; Abrams, Keith; Sculpher, Mark
Abstract : Objective: To assess the cost effectiveness of primary angioplasty, compared with medical management with thrombolytic drugs, to achieve reperfusion after acute myocardial infarction (AMI) from the perspective of the UK NHS. Design: Bayesian evidence synthesis and decision analytic model. Methods: A systematic review was conducted and Bayesian statistical methods used to synthesise evidence from 22 randomised control trials. Resource utilisation was based on UK registry data, published literature and national databases, with unit costs taken from routine NHS sources and published literature. Main outcome measure: Costs from a health service perspective and outcomes measured as quality-adjusted life years (QALYs). Results: For the base case, the incremental cost-effectiveness ratio of primary angioplasty was £9241 for each additional QALY, with a probability of being cost effective of 0.90 for a cost-effectiveness threshold of £20 000. Results were sensitive to variations in the additional time required to initiate treatment with primary angioplasty. Conclusions: Primary angioplasty is cost effective for the treatment of AMI on the basis of threshold cost-effectiveness values used in the NHS and subject to a delay of up to about 80 minutes. These findings are mainly explained by the superior mortality benefit and the prevention of non-fatal outcomes associated with primary angioplasty for delays of up to this length.